THE FIRST TWO CASES OF CHRONIC HEPATITIS ASSOCIATED WITH TORQUE TENO MIDI VIRUS (TTMDV), GENUS GAMMATORQUEVIRUS - I. A. Morozov; L. Yu. Ilchenko; K. K. Kyuregyan; A. A. Karlsen; E. S. Fediukina; I. G. Fedorov; N. V. Petrenko (Архивъ внутренней медицины, 2017)
The prevalence of Anelloviridae virus is high among population in many countries. The hepatotropic and hepatopathogenic features were confirmed in some genotypes of this family. Two chronic hepatitis B clinical cases associated with Torque teno midi virus (TTMDV, genus Gammatorquevirus) in the absence of other Anelloviruses and hepatotropic viruses (HBV, HCV, GBV -C, CMV) were described by using of molecular-biological, histopathological, immu nohistochemical and electron microscopy methods.